(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The paper considers the problem of communicative orientation in the Ukrainian language teaching, outlines the main ways of achieving the goals of language education in today’s basic school conditions, gives the examples of the exercises, aimed at students’ communicative skills building whilst studying morphology.